2006
DOI: 10.1093/annonc/mdl085
|View full text |Cite
|
Sign up to set email alerts
|

Improved incidence of pT0 downstaged surgical specimens in locally advanced rectal cancer (LARC) treated with induction oxaliplatin plus 5-fluorouracil and preoperative chemoradiation

Abstract: Short-intense induction FOLFOX-4 significantly improves pathologic complete response in LARC patients treated with tegafur-sensitized preoperative chemoradiation. The 44% rate of pT(0)-(1) specimens observed in the oxaliplatin group should impulse innovative surgical approaches to promote ano-rectal sphincter conserving protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 52 publications
4
40
1
1
Order By: Relevance
“…Calvo et al [17] explored short-term, intense induction with FOLFOX4 (two cycles) before conventional CRT in patients with locally advanced rectal cancer, and reported that it improved tumor downstaging in comparison with CRT alone, based on their historical results. This strategy achieved a 29% pathological complete response rate.…”
Section: Discussionmentioning
confidence: 99%
“…Calvo et al [17] explored short-term, intense induction with FOLFOX4 (two cycles) before conventional CRT in patients with locally advanced rectal cancer, and reported that it improved tumor downstaging in comparison with CRT alone, based on their historical results. This strategy achieved a 29% pathological complete response rate.…”
Section: Discussionmentioning
confidence: 99%
“…This therapeutic strategy is potentially effective for a select subgroup of patients without early metastasis who are eligible to receive CRT. This approach of introducing systemic treatment (chemotherapy) prior to locoregional treatment (surgery or radiotherapy) has been investigated in other gastrointestinal cancers, such as esophageal, gastric, and rectal cancers, with varying degrees of success [12][13][14][15]. Several studies evaluated the benefit not only of neoadjuvant chemotherapy before surgery in resectable PC, but also of induction chemotherapy before concurrent CRT in locally advanced PC [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…One of the earliest trials to investigate this assessed the use of 5-FU with concurrent mitomycin-C in the context of neoadjuvant radiotherapy with optimistic results [24]. However, in the era of chemotherapeutic agents with more specific activity against colorectal malignancies, various non-randomized trials have demonstrated a significant benefit of FOLFOX (5-FU/Folinic acid/Oxaliplatin) and CapeOx (Capecitabine and Oxaliplatin) in tumor down-staging, with no demonstrable concern of tumor progression [25,26]. In order to test this, Maréchal and colleagues conducted a trial in which patients with locally advanced rectal cancers were randomized to the control of neoadjuvant chemoradiation with radiosensitizing infusional 5-FU vs short-course induction FOLFOX chemotherapy (2 cycles) followed by neoadjuvant chemoradiation as performed in the control arm.…”
Section: Outcomes With Varying the Type Of Chemotherapymentioning
confidence: 99%